Technology assessment on the computerization of Pre-CRS records of the Office of the University Registrar, University of the Philippines Diliman - Abella, Franklin H. Jr.; Imbang, Glen (Quezon City University of the Philippines Diliman, 2009)
The Office of the University Registrar is a vital arm of the University. It is the official recorder and keeper of records of the students. As official recorder, it serves as Secretariat in different administration committees, such as the Executive Committee, the Curriculum Committee, the Committee on Student Progress, Admission and Graduation, and in the University Council meetings, and also acts as steering committee of the University Council Committees. As a repository of decades of student records, the OUR is both a source and resource of data that can be used for various researches. In order to improve the systems of acquiring, recording, storing and retrieving information, full computerization of records, admission, registration and other procedures are in order. The OUR have all the records of all UP students. The records from 1908 until 1965 are stored in the archives of the Main Library. The records from 1966 to the present are kept by the OUR.
In partial fulfillment of the requirements in TM 299.2
Thesis
Keywords: Office of the University Registrar, University of the Philippines Diliman; Technology assessment; Education -- Data processing